A comparative study on Suzuki‐type 11C‐methylation of aromatic organoboranes performed in two reaction media. (20th July 2021) - Rokka, Johanna; Nordeman, Patric; Roslin, Sara; Eriksson, Jonas
Abstract : The Suzuki‐type cross coupling reaction is a palladium‐mediated multistep reaction that has been used to synthesize several 11 C‐labeled tracers for PET. However, the impact of the selected organoborane reagent and reaction medium on the radiochemical yield (RCY) has not been thoroughly investigated. To bridge this gap, we studied the synthesis of 1‐[ 11 C]methylnaphthalene using four different organoborane precursors in reactions performed in DMF/water and THF/water. In the synthesis of 1‐[ 11 C]methylnaphthalene, the best radiochemical yields (RCYs), approximately 50%, were obtained with boronic acid and pinacol ester precursors, whereas less than 4% RCY was obtained when performing the reaction with the N‐methylimidodiacetic acid boronic ester (MIDA ester) precursor. 1‐[ 11 C]methylnaphthalene was obtained in higher yields in almost all syntheses performed in THF/water as compared to DMF/water. This observation was in line with previously reported results for [ 11 C]UCB‐J, a tracer for the synaptic vesicle glycoprotein 2A (SV2A) receptor, that also was obtained in higher RCY when synthesized in THF/water. The same trend was observed with [ 11 C]cetrozole, where the RCY was more than doubled in THF/water compared to the previously published synthesis performed in DMF. These results suggest that THF/water could be the preferred reaction medium when producing PET tracers via the Suzuki‐type coupling reaction. Abstract : The synthesis of 1‐[ 11 C]methylnaphthalene was studied using different organoboranes in reactions performed in DMF/water and THF/water. Higher radiochemical yield (RCY) of 1‐[ 11 C]methylnaphthalene was obtained in syntheses performed in THF/water compared to DMF/water. The same trend was observed in the synthesis of [ 11 C]cetrozole and [ 11 C]UCB‐J; RCY was more than doubled in THF/water compared to the original reaction medium. These results suggest that THF/water could be the preferred reaction medium when producing PET tracers via the Suzuki‐type coupling reaction.